Innovation In Public Services Through The "Mobile SIM" Program: A Qualitative Study In The Indonesian National Police - Tinto Adi Nugraha; Bintoro Wardiyanto; Erna Setijaningrum (INJECT (Interdisciplinary Journal of Communication), 2025)
This research aims to explore and analyze public service innovations in the "Mobile SIM program" by the Indonesian National Police. Through a qualitative approach, this study explores perceptions, experiences, and challenges in the implementation of this service from the perspective of police personnel and the user community. The results of the study show that the "Mobile Driver's License" is a tangible manifestation of public service innovation based on community needs, but still faces obstacles such as limited human resources, facilities, and the use of digital technology. Recommendations are given to improve the effectiveness and reach of services through strengthening the capacity of Human Resources, cross-sector collaboration, and integration of public service information systems. This service provides a more flexible access alternative for the public in renewing their Driver's License, while reflecting the efforts of state institutions to bring services closer to the public.